Instrucción para la transición cognoscitiva : el caso de física - Bascones, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Results of the evaluation of an instructional system which take account of how past experiences and knowledge influence perception, comunication and learning are presented. Experimental activities, problem solving, and discussion period for contrasting previous and new learning have been emphasized in the instructional design. Instructional strategies such as conceptual maps, Gowin's heuristic V and problem solving have been used. The instructional system was evaluated with a sample of 76 secondary school. The selection was based on previous knowledge of optics and the determination of misconceptions in cognitive structure of the same population. Results show relevant differences in tests between controlled and experimental groups.